Vaccination and Human Health - O. V. Shamsheva (Детские инфекции (Москва))
Vaccination is crucial in maintaining the health of the nation. Achieved outstanding successes in the fight against childhood infections. The article shows the prospects of using the method of vaccination including the treatment and prevention of dysbiotic disorders, for the treatment and prevention of immune disorders, the chronicity of the process, increase of immune response. Described tactic vaccination of various population groups.